2021
DOI: 10.3390/md19030139
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Analytical Platforms of NMR Spectroscopy and LCMS Analysis in the Metabolite Profiling of Isochrysis galbana

Abstract: This study was designed to profile the metabolites of Isochrysis galbana, an indigenous and less explored microalgae species. 1H Nuclear Magnetic Resonance (NMR) spectroscopy and Liquid Chromatography-Mass Spectrometry (LCMS) were used to establish the metabolite profiles of five different extracts of this microalga, which are hexane (Hex), ethyl acetate (EtOAc), absolute ethanol (EtOH), EtOH:water 1:1 (AqE), and 100% water (Aq). Partial least square discriminant analysis (PLS–DA) of the generated profiles rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 95 publications
5
8
0
Order By: Relevance
“…However, the increment measured was not significant, probably due to high variations between rep-licates. The increment of ethanol could be associated with glycolysis due to high glucose content in IG as reported previously in the relative quantification of metabolites identified [73]. Previous studies have proven the impact of ethanol on immunomodulatory properties [87,88].…”
Section: Upregulated Metabolismsupporting
confidence: 67%
See 1 more Smart Citation
“…However, the increment measured was not significant, probably due to high variations between rep-licates. The increment of ethanol could be associated with glycolysis due to high glucose content in IG as reported previously in the relative quantification of metabolites identified [73]. Previous studies have proven the impact of ethanol on immunomodulatory properties [87,88].…”
Section: Upregulated Metabolismsupporting
confidence: 67%
“…In the present study, isoleucine is one of the metabolites with a significant increment in fish spleen cells after being fed with an IG-supplemented diet when compared to the commercial diet. The isoleucine increase could be related to its presence with other amino acids in IG which successfully identified via NMR in polar solvents as reported before [73]. A recent study found isoleucine enhanced growth performance and intestinal immunology of hybrid catfish.…”
Section: Upregulated Metabolismmentioning
confidence: 52%
“…However, there is no information available in the literature about the spectrum data for this compound. The obtained data were compared to the related structure, arachidic acid fatty acid [ 46 ]. Hence, according to the NMR inspection, mass data, and literature data, the structure of 1 was confirmed as arachidyl arachidate, which is known as a one of the natural waxes found in plants and microorganisms [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This carotenoid is present in a variety of macroalgae, but also in a multitude of species of microalgae such as Isochrysis sp. (Haptophyta), Odontella aurita [54,55], Nitzschia laevis (formerly Nitzschia amabilis) [56], and Chaetoceros neogracili (formerly Chaetoceros gracilis) (Bacillariophyta), the coccolithophore Pleurochrysis carterae (Haptophyta, Coccolithophyceae) [57], Phaeodactylum tricornutum (Bacillariophyta) [46], and the microalga strain Pavlova sp. OPMS 30543 (Haprophyta) [58].…”
Section: Fucoxanthinmentioning
confidence: 99%